Material characterisation of nanowires with intrinsic stress - Boland, John (My University, 2017)
When fabricating nanowires in a doubly-clamped beam configuration it is possible for a residual axial stress to be generated. Here, we show that material characterisation of metal and semiconductor nanowires subjected to residual axial stress can be problematic. Benchmark measurements of the Young’s modulus of nanowires are performed by sectioning a doublyclamped nanowire into two cantilevered wires, eliminating residual axial stress. Use of models for doubly-clamped beams that incorporate the effects of residual stress are found to lead to ambiguity in the extracted Young’s modulus as a function of displacement fit range, even for nanowires with no residual stress. This is due to coupling of bending and axial stress effects at small displacements, and the limited displacement range of force curves prior to fracture or plastic deformation. This study highlights the importance of fabricating metal and semiconductor nanowires that exhibit little or no residual axial stress for materials characterisation.
Keywords: Residual stress; doubly-clamped; Nanowires; Young’s modulus; Euler-Bernoulli; Nanoscience & Materials